THE INFLUENCE OF LIQUIDITY, SOLVENCY AND EFFICIENCY ON PROFITABILITY AT PT BANK MUAMALAT INDONESIA YEAR 2017-2022 - marjan marjan (Al-Qardhu, 2024)
The aim of this research is to determine the influence of the Financing Deposit Ratio (FDR), Debt Equity Ratio (DER), and Operating Costs Operating Income (BOPO) variables on Return On Assets (ROA) at Bank Muamalat Indonesia in 2017-2022. This research is quantitative research. The type of data used is in the form of quarterly and annual financial reports obtained from the official Bank Muamalat Indonesia website from 2017-2022. The analytical methods used are classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R2 test). From the research results it can be concluded that based on partial test results (t test), the FDR variable shows that FDR has a positive direction and has a significant influence on ROA. The DER variable shows that DER has a positive direction and does not have a significant effect on the ROA variable. Meanwhile, the BOPO variable has a negative and significant effect on (ROA). Then based on the simultaneous test results (f test), the three variables, namely FDR, DER, and BOPO simultaneously have a significant effect on ROA.